Designing and conducting a forest inventory - case 9th National Forest Inventory of Finland - Tomppo, Erkki; Heikkinen, Juha.; Henttonen, Helena M.; Ihalainen, Antti; Katila, Matti; Mäkelä, Helena; Tuomainen, Tarja; Vainikainen, Nina.; SpringerLink (Online service). (Dordrecht, Netherlands Springer Netherlands, 2011)
Reliable information on forest resources and the status of forests at the national level is required for various purposes, such as making strategic decisions, formulating regulations and recommendations for forest management, aimed at ensuring the availability of sufficient supply of timber for the forest industries as well as in their strategic planning of investments. It is also essential in planning forest protection and for maintaining biodiversity. Global agreements, such as the Kyoto Protocol, increasingly rely on national forest statistics.   National Forest Inventories in Finland have evolved gradually over a period of one hundred years, first with a trial inventory in the 1910s, and since the 1920s, with operative inventories. The sampling design and estimation methods have been continuously revised to correspond with inventory techniques and the available infrastructure. The content, as well as the collected data and variables employed, are constantly adapted to the users' needs. Co-operation with the inventories of other countries, particularly with those of the Nordic countries, has supported these developments.   This book demonstrates in detail all phases of the 9th National Forest Inventory of Finland (1996-2003): the planning of the sampling design, measurements, estimation methods and results. The inventory knowledge accumulated during almost one hundred years is consolidated in the book. The purpose of the numerous examples of results is to demonstrate the diversity of the estimates and content of a national forest inventory. The authors hope that the book will help in designing and conducting any large area forest inventory.
Preface -- Acknowledgements -- 1. Introduction -- 2. Design and Measurements -- 3. Estimation Methods -- 4. Results -- 5. Discussion -- Appendix -- References -- Subject Index.
Electronic reproduction.
Keywords: Forest surveys -- Finland; Electronic books